Pengendalian Kualitas Proses Produksi Sepatu Heels Dalam Upaya Mencapai Target Produksi Pada CV Ghealsyshoes Malang (Program Studi Ilmu Administrasi Bisnis, 2022)
The purpose of this study was to identify, describe and analyze the quality control of the production process for heels in an effort to achieve production targets at CV Ghealsyshoes Malang. The company engaged in manufacturing CV Ghealsyshoes is a local company in Indonesia that produces various kinds of shoes, especially women's shoes. Based on data and facts in the field, it was found that in one year of production, heels still experience product defects caused by problems that occur in the production process, which is an average of 2.75%. Problems in the production process are caused by several factors at the input or input stage such as raw materials, performance of tools and machines, and labor. The results showed that quality control at CV Ghealsyshoes was divided into three stages. The first stage is the process of arrival of raw materials which aims to select and filter the raw materials ordered from suppliers, the second stage is the stage of the production process which aims to avoid product damage due to raw materials that do not comply with predetermined criteria and maintain the production process so that running smoothly, the third is the stage of the product release process which aims to maintain and supervise the process that has passed the production process in order to avoid product defects that will later be used by consumers. Keyword: Qualitiy Control, Production Process, Production Targets